2022
DOI: 10.1002/advs.202202153
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healable, Self‐Repairable, and Recyclable Electrically Responsive Artificial Muscles

Abstract: Elastomers with high dielectric permittivity that self‐heal after electric breakdown and mechanical damage are important in the emerging field of artificial muscles. Here, a one‐step process toward self‐healable, silicone‐based elastomers with large and tunable permittivity is reported. Anionic ring‐opening polymerization of cyanopropyl‐substituted cyclic siloxanes yields elastomers with polar side chains. The equilibrated product is composed of networks, linear chains, and cyclic compounds. The ratio between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…To the best of our knowledge, the last report involving the development of a dielectric elastomer with self-healing properties belongs to Szczepanski and co-workers, which, starting from cyclic siloxanes bearing nitriles as dipolar pendant groups achieved the synthesis of silicone-based elastomers with high and modulable permittivity and self-healing capability, employing a simple one-step methodology through anionic ringopening polymerization. 363 At the end of the process, the equilibrated macromolecular network, it is composed of linear chains and cyclic compounds covalently attached, whose thermal and mechanical properties showed to be highly dependent on the cross-linking density, as well as the amount of dipolar structures. Regarding mechanical properties, tensile tests revealed that an increment of the cross-linker composition in the formulation led to a depletion of the elongation at break value, falling from 59 ± 3% to 41 ± 3%, while at the same time a rise of the Young's modulus up to 202 ± 10 kPa was achieved.…”
Section: Self-healing Electric Actuatorsmentioning
confidence: 99%
“…To the best of our knowledge, the last report involving the development of a dielectric elastomer with self-healing properties belongs to Szczepanski and co-workers, which, starting from cyclic siloxanes bearing nitriles as dipolar pendant groups achieved the synthesis of silicone-based elastomers with high and modulable permittivity and self-healing capability, employing a simple one-step methodology through anionic ringopening polymerization. 363 At the end of the process, the equilibrated macromolecular network, it is composed of linear chains and cyclic compounds covalently attached, whose thermal and mechanical properties showed to be highly dependent on the cross-linking density, as well as the amount of dipolar structures. Regarding mechanical properties, tensile tests revealed that an increment of the cross-linker composition in the formulation led to a depletion of the elongation at break value, falling from 59 ± 3% to 41 ± 3%, while at the same time a rise of the Young's modulus up to 202 ± 10 kPa was achieved.…”
Section: Self-healing Electric Actuatorsmentioning
confidence: 99%
“…, light, temperature, pH, electrochemical, pressure, and humidity). 1–39 These actuators have significant application potential in a range of smart devices and in the field of soft robotics. 40–59 Among the various artificial muscles, twisted-fiber artificial muscles have received widespread research attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, conductive hydrogels inevitably face mechanical challenges during daily usage (such as large stretching and external punctures), leading to the deterioration of their sensing performance because the structural integrity of the hydrogels is gradually destroyed with time. Recently, researchers have studied energy-dissipation methods to improve the mechanical properties of hydrogels. These mainly include double-network hydrogels, nanoparticle-reinforced hydrogels, and micellar-cross-linked hydrogels . However, these high-toughness hydrogels are usually limited by their self-adhesiveness.…”
Section: Introductionmentioning
confidence: 99%